Problems of education: fiction and reality - Voronichev, Oleg Evgen'evich; Voronicheva, Olga Viktorovna (Современное образование, 2022)
The problems of education are analyzed in close relationship with the cultural priorities of the mass consumption society.. Attention is focused on the fact that a teacher should not just be a translator of knowledge, but first of all a spiritual mentor, educator, bearer of true cultural values. Rapid scientific progress, the result of which has been noticeable, especially in recent decades, the filling of the everyday and cultural space of society with various technical innovations, has clearly actualized the problem of interaction, correlation and significance of technogenic and humanitarian components in the life of man and society. The sphere of education has turned out to be at the forefront of the confrontation of these spheres, with the obvious and aggressive dominance of the first. Signs of the crisis of modern humanitarian education are considered in the mirror of R. Young's science fiction story "30 Days in September", which describes the quite probable and already tangible consequences of the choice of a technogenic path of development by society for culture in general and the educational sphere in particular. Since material benefits are achieved and accumulated much more easily than spiritual ones, humanity needs to think about the obvious imbalance of these components of our life today and build an education system in such a way that the priority is not the desire for unified material benefits inherent in a mass consumption society, but for genuine spiritual values necessary for the development and improvement of a person as a whole personalities.